Bioorthogonal organic chemistry in living cells: novel strategies for labeling biomolecules. - van Swieten, P; Leeuwenburgh, M; Kessler, B; Overkleeft, H (2005)
The chemical labeling of biomolecules continues to be an important tool for the study of their function and cellular fate. Attention is increasingly focused on labeling of biomolecules in living cells, since cell lysis introduces many artefacts. In addition, with the advances in biocompatible synthetic organic chemistry, a whole new field of opportunity has opened up, affording high diversity in the nature of the label as well as a choice of ligation reactions. In recent years, several different two-step labeling strategies have emerged. These rely on the introduction of a bioorthogonal attachment site into a biomolecule, then ligation of a reporter molecule to this site using bioorthogonal organic chemistry. This Perspective focuses on these techniques, their implications and future directions.